Social separation and diazepam withdrawal increase anxiety in the elevated plus-maze and serotonin turnover in the median raphe and hippocampus - Santos, Lucinéia dos [UNESP]; Andrade, Telma Gonçalves Carneiro Spera de [UNESP]; Graeff, Frederico G. (Sage Publications Ltd, 2010)
The present work aimed to evaluate the effects of social separation for 14 days (chronic stress) and of withdrawal from a 14-day treatment with diazepam (acute stress) on the exploratory behaviour of male rats in the elevated plus-maze and on serotonin (5-hydroxytryptamine) turnover in different brain structures. Social separation had an anxiogenic effect, evidenced by fewer entries into, and less time spent on the open arms of the elevated plus-maze. Separation also selectively increased 5-hydroxytryptamine turnover in the hippocampus and median raphe nucleus. Diazepam withdrawal had a similar anxiogenic effect in grouped animals and increased 5-hydroxytryptamine turnover in the same brain structures. Chronic treatment with imipramine during the 14 days of separation prevented the behavioural and neurochemical changes caused by social separation. It is suggested that the increase in anxiety determined by both acute and chronic stress is mediated by the activation of the median raphe nucleus-hippocampal 5-hydroxytryptamine pathway.
Keywords: social separation; anxiety; elevated plus-maze; serotonin; diazepam withdrawal; imipramine